Uganda : Fifth Review Under the Policy Support Instrument and Request for Waiver of an Assessment Criterion and Modification of Assessment Criteria-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report, 2015)
This paper discusses Uganda's Fifth Review Under the Policy Support Instrument (PSI) and Request for Waiver of an Assessment Criterion and Modification of Assessment Criteria. The economy of Uganda has fared well in a difficult environment. Program performance under the PSI was generally positive. All end-June and continuous quantitative assessment criteria were observed, with one exception, and so were most indicative targets. Inflation remained within the bands of the consultation clause. An unprecedented increase in tax revenue was a key achievement. However, further progress on structural reforms is needed. The authorities are rightly adjusting the policy mix. The IMF staff recommends completing the fifth review under the PSI.